The Characteristics of Chemosensory and Opsin Genes in Newly Emerged and Sexually Mature Agrilus planipennis, an Important Quarantine Forest Beetle - Shen, Sifan; Fan, Zhizhi; Zhang, Xun; Kong, Xiangbo; Liu, Fu; Zhang, Zhen; Zhang, Xinhua; Hu, Xiumei; Zhang, Sufang (Frontiers in Genetics, 2021)
The emerald ash borer (EAB), Agrilus planipennis, is a highly destructive quarantine pest. The olfactory and visual systems of A. planipennis play different but critical roles at newly emerged and sexually mature stages; however, the molecular basis underlying these differences remain unclear. Consequently, based on deep transcriptome sequencing, we evaluated the expression levels of chemosensory-related proteins and opsins at the two developmental stages of A. planipennis. We found 15 new chemosensory-related genes in our transcriptome assembly compared with the previous genome assembly, including 6 that code for odorant-binding proteins (OBPs) and 9 for chemosensory proteins (CSPs). The expression of several chemosensory-related genes (OBP7, OBP10, CSP1, and CSP12) differed markedly between newly emerged and sexually mature A. planipennis, which may be related to the sensing of host volatiles or mating olfactory cues. We also found that the expression of UV opsin 2 and LW opsin 1 was higher in sexually mature male A. planipennis, which may be associated with their strong visual mate detection ability. This study forms the basis for further investigation of the chemosensory and visual system of A. planipennis, and these differentially expressed genes between newly emerged and sexually mature stages may serve as targets for the management of this destructive forest pest after sexual maturity.